عادات النكاح في ضوء الشريعة الإسلامية :‏ ‏جزيرة جاوة - أندونيسيا نموذجا /‏ - بنا، حسن أحمد (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This research studies the traditional marriage ceremony in the Central Java, Indonesia in the light of Islamic Jurisprudence. In explaining the five chapters of the thesis, the researcher adopted descriptive and analytical methodologies to elaborate and explain marriage in its entirety including the engagement, the solemnisation ceremony, and the marriage reception. Comparative methodology was utilized to combine the congruence of Central Java's traditional marriage with Islamic Law. In the conclusion of the study the researcher compared and concluded that in traditional wedding ceremonies, some elements are acceptable while others are in violation of Islamic teachings. Generally, traditional marriage is performed within the Islamic condition and does not contradict with Islamic law, except for some practices associated with inappropriately inherited traditions. Moreover those traditions can be categorized under shirk (polytheism) and bid'ah (unlawful or innovation in Islam) that contradict with Islamic teachings. It is necessary to correct those inappropriate traditions that satisfy the Central Java community and in Indonesia as whole, more attention should be given to the behaviour associated with Islamic values.